(untitled) (Italian Journal of Public Health, 2006)
Background: Stress is a major cause of sickness absence and the health care sector appears to be especially at risk. This cross sectional study aimed to identify the risk factors for absence due to self-reported stress among health care employees. Methods: 225 health care employees were categorized into two groups based on presence or not of self-rated sickness absence for stress. Questionnaire data and stress sensitive hormones measurements were used. Results: Employees with stress related sick leave experienced worse health, poorer work satisfaction as well as worse social and home situations than those employees without stress-related sick leave. No-significant differences were identified regarding stress-sensitive hormones. The risk for employees, not satisfied at work, of becoming absent due to stress was approximately three fold compared to those who reported being satisfied (OR 2.8, 95% confidence interval; (CI) 1.3 - 5.9). For those not satisfied with their social situation, the risk for sickness absence appeared to be somewhat higher (OR 3.2; CI 1.2 - 8.6). Individual factors such as recovery potential and meaning of life as well as work related factors such as skill development and work tempo predicted employee’ s work satisfaction. Conclusions: Based on cross sectional data, work-site and individual factors as well as social situations appear to increase the risk for absence due to stress among health care employees. Lower recovery potential, higher work tempo and poor leadership appeared to be related to the high degree of work related exhaustion experienced by employees.